Oxo-atom transfer reactions of transition metal complexes in catalytic oxidation with O2 on the light of some recent results in molybdenum-oxo chemistry - H. Arzoumanian; R. Bakhtchadjian (ՀՀ ԳԱԱ հրատ.)
The oxo-atom transfer reactions, which are one of the important fields of transition metals coordination chemistry, are widely spread in nature and used in chemical and pharmaceutical industries. This review presents some aspects of the application of oxo-atom transfer reactions in catalytic oxidation. Անցման շարքի մետաղական կոմպլեքսների օքսո-ատոմի փոխանցմամբ ընթացող կատալիտիկ օքսիդացման ռեակցիաները լայն տարածում ունեն կենդանի բնության մեջ և կիրառվում են քիմիական և դեղագործական արդյունաբերություններում: Սույն աշխատանքում ներկայացված են կատալիտիկ օքսիդացման համակարգերում օքսոատոմի փոխանցմամբ ընթացող ռեակցիաների որոշ առանձնահատկություններ: Реакции переноса oкco-атома комплексов переходных металлов в окислительных каталитических процессах широко распространены в живой природе и применяются в химической и фармацевтической промышленности. В этой работе представлены некото- рыe особенности применения реакций переноса oкco-атома в тех окислительных каталитических cистемax, в которыx в качестве окислителя используется молекулярный кислород.
Keywords: Physical Chemistry